Alkylamine screening and zinc doping of highly luminescent 2D tin-halide perovskites for LED lighting. Issue 4 (28th January 2021) - Liu, Yao; Wang, Aifei; Wu, Jiajing; Wang, Chuying; Li, Ziliang; Hu, Guangcai; Sui, Shiqi; She, Jia-Xin; Meng, Wen; Li, Weiqiang; Deng, Zhengtao
Abstract : Highly luminescent and stable two-dimensional tin-halide perovskites for LED lighting applications were achieved through alkylamine screening and zinc doping. Abstract : In recent years, two-dimensional (2D) layered tin halide perovskites have attracted much attention due to their excellent luminescence properties compared with their three-dimensional (3D) analogs. Here, we synthesized 2D perovskites of the form (RNH3 )2 SnBr4 through a facile hot-injection approach without the use of toxic tri- n -octylphosphine (TOP) as the solvent. We found that these compounds have strong photoluminescence (PL) emission with high PL quantum yields (QY) of 35% ((C6 H13 NH3 )2 SnBr4 ), 82% ((C8 H17 NH3 )2 SnBr4 ), 60% ((C12 H25 NH3 )2 SnBr4 ) and 50% ((C18 H35 NH3 )2 SnBr4 ). Among them, ((C6 H13 NH3 )2 SnBr4 ) was synthesized for the first time; however, (C18 H36 NH3 )2 SnBr4 perovskites showed the best stability with a PL QY decrease of less than 1% after 30 days under ambient air and humidity conditions. In addition, other 2D (C8 H17 NH3 )2 SnX4 (X = Br, I, or mixture) perovskites were prepared by adjusting the halide ratio, resulting in spectral tunability from yellow to red. Interestingly, through Zn 2+ doping, the morphology became more uniform, and the PL stability was significantly improved. Finally, we used Zn 2+ -doped (C8 H17 NH3 )2 SnBr4 yellow phosphor to fabricate UV-pumped yellow LEDs. We expect these 2D perovskites to be promising phosphors in future solid-state lighting and display technologies.